Playful strategies for the development of fine motor skills in children from an initial educational institution - Quispe Morales, Freddy (2021)
The research work that is presented was developed with the objective of verifying the influence of playful strategies on the development of fine motor skills in children from an initial educational institution. It is an investigation carried out from the quantitative approach, of an experimental type and specified in a pre-experimental design. Likewise, for data collection, the observation sheet was used as an instrument, which was applied to a sample of 20 children of 5 years of age of the initial education level. The statistician used for the corresponding hypothesis test was Wilcoxon as it is ordinal scale data. The results obtained as a result of the research carried out allow us to conclude that playful strategies significantly influence the development of fine motor skills in 5-year-old children of the initial education level, a result that is corroborated with the level of significance that is equal to 0.000 <0.05 so it is allowed to reject the null hypothesis and accept the alternative hypothesis.